2013
DOI: 10.1053/j.ajkd.2012.11.034
|View full text |Cite
|
Sign up to set email alerts
|

Association of Cardiac Troponin T With Left Ventricular Structure and Function in CKD

Abstract: Background Serum cardiac troponin T (cTnT) is associated with increased risk of heart failure and cardiovascular death in several population settings. We evaluated associations of cTnT with cardiac structural and functional abnormalities in a cohort of chronic kidney disease (CKD) patients without heart failure. Study Design Cross-sectional. Setting & Participants Chronic Renal Insufficiency Cohort (CRIC; N= 3,243) Predictor The primary predictor was cTnT. Secondary predictors included demographic and cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 39 publications
1
38
2
Order By: Relevance
“…Our findings are consistent with a previous analysis of 8000 participants with albuminuria in the Prevention of Renal and Vascular End-Stage Disease (PREVEND) Study, which showed that hsTnT was associated with incident cardiovascular events, even after adjustment for eGFR and severity of albuminuria. 17 Prior studies have also shown that elevated hsTnT is associated with abnormal left ventricular structure and function in patients with 12,18 and without CKD. 11 Among participants in the CRIC Study, those with the highest quartile of detectable hsTnT had a 2-fold higher odds of LVH compared with those in the lowest quartile.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with a previous analysis of 8000 participants with albuminuria in the Prevention of Renal and Vascular End-Stage Disease (PREVEND) Study, which showed that hsTnT was associated with incident cardiovascular events, even after adjustment for eGFR and severity of albuminuria. 17 Prior studies have also shown that elevated hsTnT is associated with abnormal left ventricular structure and function in patients with 12,18 and without CKD. 11 Among participants in the CRIC Study, those with the highest quartile of detectable hsTnT had a 2-fold higher odds of LVH compared with those in the lowest quartile.…”
Section: Discussionmentioning
confidence: 99%
“…Our results expand on these prior studies by reporting a strong association between elevated NT-proBNP and clinically relevant changes in kidney function before the onset of clinically diagnosed CKD among a large, multicenter, community-based cohort of elderly adults free of HF at baseline across a range of kidney function. Concentrations of TnT may become elevated in response to myocardial injury, myocardial remodeling, or LVH (14,15). Very few studies have examined associations of elevations in TnT and decline in kidney function.…”
Section: Discussionmentioning
confidence: 99%
“…NT-proBNP is secreted into the circulation from cardiac myocytes in response to stimuli, such as pressure or volume overload (13). Similarly, TnT concentrations may become elevated in response to myocardial injury, myocardial remodeling, or left ventricular hypertrophy (LVH) (14,15). Elevated NT-proBNP and TnT concentrations may serve as early markers of abnormal cardiac physiology, which may also be associated with poor kidney outcomes as well.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protocol for obtaining echocardiograms has been described previously (23,24). LVMI was calculated on the basis of the area-length formula and indexed to height 2.7 (25).…”
Section: Study Outcomes-target Organ Damagementioning
confidence: 99%